(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2017)
This is a case report of a suicidal hanging with the rare finding of a split laceration as a peri-ligature injury. The plausible mechanism of the injury is the compressive force acting almost vertically on the neck structures, splitting the tissue that is supported by the underlying thyro-hyoid complex.